1999
DOI: 10.1074/jbc.274.36.25792
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation at Mammalian Replication Origins

Abstract: In Escherichia coli, DNA methylation regulates both origin usage and the time required to reassemble prereplication complexes at replication origins. In mammals, at least three replication origins are associated with a high density cluster of methylated CpG dinucleotides, and others whose methylation status has not yet been characterized have the potential to exhibit a similar DNA methylation pattern. One of these origins is found within the ϳ2-kilobase pair region upstream of the human c-myc gene that contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 103 publications
0
36
0
Order By: Relevance
“…Another study suggests a slightly longer delay, but showed methylation to be complete by the time the fork had progressed 4 kb. 48,49 DNMT1 co-localizes with PCNA and BrdU to fine nuclear speckles representing early S-phase replication foci and interacts with PCNA in whole cell extracts through a peptide near the amino-terminus (amino acids 163-174) that is distinct from the replication targeting domain described above. 18 The interaction of PCNA with DNMT1 may act to tether DNMT1 to the DNA, thus endowing DNMT1 with processivity by facilitating its tracking along the newly-synthesized DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggests a slightly longer delay, but showed methylation to be complete by the time the fork had progressed 4 kb. 48,49 DNMT1 co-localizes with PCNA and BrdU to fine nuclear speckles representing early S-phase replication foci and interacts with PCNA in whole cell extracts through a peptide near the amino-terminus (amino acids 163-174) that is distinct from the replication targeting domain described above. 18 The interaction of PCNA with DNMT1 may act to tether DNMT1 to the DNA, thus endowing DNMT1 with processivity by facilitating its tracking along the newly-synthesized DNA.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation at specific cytosine residues might also serve as a signal recognized by the replication machinery, and this may lead to initiation of replication at more specific genomic sites. This mechanism may be used only by a subset of origins because not every origin of replication appears to have methylated CpG sequences (31).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DNMT1 also interacts with PCNA at the replication fork (17)(18)(19) and a fraction of CpGs are subject to maintenance methylation prior to maturation of Okazaki fragments on the lagging strand (20,21). This suggests that DNMT1 may need to be present immediately behind the replication fork in order to promote efficient methylation of nascent DNA prior to its packaging into nucleosomes.…”
mentioning
confidence: 99%
“…Deposition of newly synthesized histones H3/H4 is mediated, at least in part, by a conserved protein known as chromatin assembly factor 1 (CAF-1), which brings histones H3/H4 to the replication fork via an interaction with the proliferating cell nuclear antigen (PCNA) (12-15). PCNA is a DNA polymerase processivity factor that forms a sliding clamp around DNA and interacts with a number of DNA replication and DNA repair proteins, many of which are constitutively present at the replication fork (16).Interestingly, DNMT1 also interacts with PCNA at the replication fork (17-19) and a fraction of CpGs are subject to maintenance methylation prior to maturation of Okazaki fragments on the lagging strand (20,21). This suggests that DNMT1 may need to be present immediately behind the replication fork in order to promote efficient methylation of nascent DNA prior to its packaging into nucleosomes.…”
mentioning
confidence: 99%